A Case Report of Cushing's Disease Presenting With Psychosis and Muscle Weakness Postpartum - Delaram Eskandari MD; Amir Ziaee MD; Seyed Hossein Samadanifard MD; Seyed Mohammad Tavangar MD; Atefe Tirkan MD; Mohammad Amin ZaeimYekeh MD (SAGE Publishing, 2023)
Cushing's syndrome is a condition leading to overproducing of cortisol by the adrenal glands. If the pituitary gland overproduces cortisol, it is called Cushing's disease. Cushing's syndrome and even Cushing's disease during and after pregnancy are rare events. There is not enough literature and guidance for managing and treating these patients. The diagnosis of Cushing's syndrome in pregnancy is often delayed because the symptoms overlap. We presented a thin 31-year-old woman, admitted 2 months after a normal-term delivery, with an atypical presentation of Cushing's disease, unusual clinical features, and a challenging clinical course. She had no clinical discriminatory features of Cushing's syndrome. Given that the patient only presented with psychosis and proximal myopathy and had an uncomplicated pregnancy, our case was considered unusual. The patients also had hyperpigmentation and severe muscle weakness which are among the less common presentations of Cushing's syndrome. Our findings suggest that an early diagnosis of Cushing's disease is important in pregnancy period for its prevalent fetal and maternal complications, and it should be treated early to optimize fetal and maternal outcomes as there is an increasing trend toward live births in treated participants.